The Equine Herpesvirus 2 E1 Open Reading Frame Encodes a Functional Chemokine Receptor - Camarda, Grazia (American Society for Microbiology, 1999)
Several herpesviruses contain open reading frames (ORFs) that encode potential homologs of eucaryotic genes. Equine herpesvirus 2 (EHV-2) is a gammaherpesvirus related to other lymphotropic herpesviruses such as herpesvirus saimiri and Epstein-Barr virus. The E1 ORF of EHV-2, a G protein-coupled receptor homolog, shows 31 to 47% amino acid identity with known CC chemokine receptors. To investigate whether E1 may encode a functional receptor, we cloned the E1 ORF and expressed it in stably transfected cell lines. We report here the identification of the CC chemokine eotaxin as a functional ligand for the EHV-2 E1 receptor. Chemokines are likely to play a role in the regulation of immune functions in equine hosts during EHV-2 infection and, via interaction with E1, may affect viral replication and/or escape from immune responses.